Uncovering the dispersion history, adaptive evolution and selection of wheat in China. Issue 1 (17th July 2017) - Zhou, Yong; Chen, Zhongxu; Cheng, Mengping; Chen, Jian; Zhu, Tingting; Wang, Rui; Liu, Yaxi; Qi, Pengfei; Chen, Guoyue; Jiang, Qiantao; Wei, Yuming; Luo, Ming‐Cheng; et al.
Summary: Wheat was introduced to China approximately 4500 years ago, where it adapted over a span of time to various environments in agro‐ecological growing zones. We investigated 717 Chinese and 14 Iranian/Turkish geographically diverse, locally adapted wheat landraces with 27 933 DArTseq (for 717 landraces) and 312 831 Wheat660K (for a subset of 285 landraces) markers. This study highlights the adaptive evolutionary history of wheat cultivation in China. Environmental stresses and independent selection efforts have resulted in considerable genome‐wide divergence at the population level in Chinese wheat landraces. In total, 148 regions of the wheat genome show signs of selection in at least one geographic area. Our data show adaptive events across geographic areas, from the xeric northwest to the mesic south, along and among homoeologous chromosomes, with fewer variations in the D genome than in the A and B genomes. Multiple variations in interdependent functional genes such as regulatory and metabolic genes controlling germination and flowering time were characterized, showing clear allelic frequency changes corresponding to the dispersion of wheat in China. Population structure and selection data reveal that Chinese wheat spread from the northwestern Caspian Sea region to South China, adapting during its agricultural trajectory to increasingly mesic and warm climatic areas.